Percutaneous Nephrolithotomy Can Reduce the Incidence of Sepsis Compared with Flexible Ureteroscopy in Treating Solitary Proximal Ureteral Stone Patients with Positive Urine Culture. (13th April 2021) - Xia, Qi-Dong; Wang, Yu-Feng; Liu, Chen-Qian; Xu, Jin-Zhou; Sun, Jian-Xuan; Xun, Yang; Li, Cong; Hu, Jia; Lu, Jun-Lin; Wang, Shao-Gang
Abstract : Background . Sepsis is a potentially lethal complication for both flexible ureteroscopy (fURS) and percutaneous nephrolithotomy (PCNL). This study is aimed at comparing the sepsis rate after fURS and PCNL and the risk factors for sepsis in patients with solitary proximal ureteral stone. Methods . We reviewed the data of patients with calculi between 10 mm to 20 mm who underwent fURS or PCNL surgery from Tongji Hospital's database. A total of 910 patients were eligible with 412 fURS cases and 498 PCNL cases. We used univariate analysis and multivariate logistic regression analysis to identify the risk factors for sepsis. Subgroup analysis was performed using logistic regression analysis. Results . In the cohort, 27 (6.6%) and 19 (3.8%) patients developed sepsis after fURS and PCNL, respectively. Multivariate analysis shows that the risk factors for sepsis are fURS (OR = 3.160, P = 0.004 ), serum   WBC ≥ 10, 000 cells/ μ L (OR = 3.490, P = 0.008 ), albumin − globulin   ratio < 1.2 (OR = 2.192, P = 0.029 ), positive urine culture (OR = 6.145, P < 0.001 ), and prolonged operation time (OR = 1.010, P = 0.046 ). Subgroup analysis was conducted using potential risk factors: stone size, serum WBC, urine culture, and albumin-globulin ratio (AGR). In subgroup of positive urine culture, patients were more likely to develop sepsis after fURS than PCNL. Conclusions . PCNL may be a better choice than fURS to reduce postoperative sepsis, especially for patients with positive urine culture.